Hoesein Djadjadiningrat’s Intellectual Contribution to the Development of Modern Historiography in Indonesia (1911-1935) - Eva Lestari; Rikza Fauzan; Tubagus Umar Syarif Hadi Wibowo (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2026)
This article examines Hoesein Djadjadiningrat’s intellectual contribution to the development of modern historiography in Indonesia between 1911 and 1935. It focuses on the formation of his thought, especially the historical methods that emerged through his works and that contributed to Indonesian historical scholarship. Using historical method—heuristics, verification, interpretation, and historiography—this study analyzes Hoesein’s writings, scholarly speeches, and relevant secondary literature. The main primary sources include Hoesein’s works from 1911 to 1935, especially Critische Beschouwing van de Sadjarah Banten. The study shows that Hoesein’s thought was shaped by social and intellectual factors, including the influence of Snouck Hurgronje and the Western orientalist tradition. However, Hoesein did not merely reproduce orientalist discourse; as a colonial subject, he reinterpreted historical knowledge through a local perspective. His works therefore mark an important moment in the emergence of modern Indonesian historiography based on source criticism, philological rigor, and historical method.